Environmental or Personal Benefit? The Role of Message Appeal and Information Type in Destination Social Media Advertisements - Japutra, Arnold; Can, Ali Selcuk; Alphun, Cihan (Sage Publications Inc, 2025)
Destinations are increasingly focusing on sustainability awareness through tourism campaigns, but effective communication remains challenging. This research, rooted in consumption value theory, delves into the influence of message appeal (environmental vs. personal benefit) and information type (objective vs. subjective) on tourists' behavioral intentions through two online experiments. Study 1 demonstrates the positive impact of environmental benefit message appeals on behavioral intentions toward destinations, both directly and indirectly, by enhancing destination brand quality and perceived green value. Study 2 validates these findings and extends the analysis to include click-through behavior as a proxy for real behavior. Our research emphasizes the importance of environmental benefits alongside objective information in destinations' sustainability messages within social media advertisements. This approach serves to bolster destination brand quality, perceived green value, and ultimately, positive behavioral intentions.
Keywords: sustainability; environmental benefits; objective information; perceived green value; destination brand quality